Analisis Daya Mengunakan EGX300 Di PT. Tiga Kreasi Indonesia - Deni Exka Saputra; Endi Permata (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
Monitoring EGX300 is to provide a screen display to view real-time data and trends with historical data records, real-time data pages that provide basic readings from selected devices in real time. This study aims to analyze the components of the EGX300, find out how to use the EGX300, find out the value of the load current, find out the value of electric power, find out the phase to phase voltage value, and find out the phase to neutral voltage value. The methods used by the author in this research are (1) observation (2) interview (3) literature study. The results of this study, namely the EGX300 component test, are the incoming load current of 4.689A, the maximum load current of 540.884A. In real power, the minimum value is -352.6KW, the incoming value is 3.2KW and the maximum value is 119.1KW. At the minimum apparent power of 00.0KVA, the entry value is 3.5KVA, and the maximum value is 377.2KVA. In phase to phase Voltage is Voltage Vab worth 388V, phase AB obtained a minimum value of 386.7V and a maximum phase AB of 385.1V, Voltage Vbc is worth 383.9V, phase BC obtained a minimum value of 383.2V and a maximum phase BC value of 385.9V and Voltage Vca is worth 378.8V, phase CA obtained a minimum value of 388.7V. In the phase to neutral voltage, Van is worth 223.6V, Voltage A-N, the minimum value is 218.9V and the maximum value of Voltage A-N is 225.8V, Voltage Vbn is worth 226.1V, Voltage B-N, the minimum value is 225.5V and the maximum value of Voltage B-N is 229.1V and Voltage Vcn is worth 221.5V, Voltage C-N, the minimum value is 220.6V and the maximum value of Voltage C-N is 225.2V